Subclade 2.2.1-Specific Human Monoclonal Antibodies That Recognize an Epitope in Antigenic Site A of Influenza A(H5) Virus HA Detected between 2015 and 2018 - Okuda, Moe; Yamayoshi, Seiya; Uraki, Ryuta; Ito, Mutsumi; Hamabata, Taiki; Kawaoka, Yoshihiro (Viruses, 2019)
Highly pathogenic avian H5 influenza viruses persist among poultry and wild birds throughout the world. They sometimes cause interspecies transmission between avian and mammalian hosts. H5 viruses possessing the HA of subclade 2.3.4.4, 2.3.2.1, 2.2.1, or 7.2 were detected between 2015 and 2018. To understand the neutralizing epitopes of H5-HA, we characterized 15 human monoclonal antibodies (mAbs) against the HA of H5 viruses, which were obtained from volunteers who received the H5N1 vaccine that contains a subclade 2.2.1 or 2.1.3.2 virus as an antigen. Twelve mAbs were specific for the HA of subclade 2.2.1, two mAbs were specific for the HA of subclade 2.1.3.2, and one mAb was specific for the HA of both. Of the 15 mAbs analyzed, nine, which were specific for the HA of subclade 2.2.1, and shared the VH and VL genes, possessed hemagglutination inhibition and neutralizing activities, whereas the others did not. A single amino acid substitution or insertion at positions 144–147 in antigenic site A conferred resistance against these nine mAbs to the subclade 2.2.1 viruses. The amino acids at positions 144–147 are highly conserved among subclade 2.2.1, but differ from those of other subclades. These results show that the neutralizing epitope including amino acids at positions 144–147 is targeted by human antibodies, and plays a role in the antigenic difference between subclade 2.2.1 and other subclades.